Death in a global age - McManus, Ruth 1965- (Palgrave Macmillan, 2013)
"Attitudes towards dying are informed by our social lives. This book explores death across different cultures, examining areas including grief and religion, life expectancy and representation. Introducing students to key debates in the field, this book shows how approaches to death are being radically reshaped in an increasingly globalized world."--Publisher's website
Keywords: pohřební zvyky; smrt -- sociologické aspekty; smrt -- sociální aspekty; smutek; umírání; funeral rites and ceremonies; death -- sociological aspects; death -- social aspects; grief; dying; monografie; monographs